PREVALENCE, PROPHYLAXIS AND TREATMENT PRINCIPLES OF PRIMARY TEETH EROSION IN CHILDREN - Alibek B. , Akhmedov (International Journal of Psychosocial Rehabilitation, 2020)
One of the urgent problems of modern dentistry is primary teeth erosion, which is in most cases connected with incorrect diagnosis and improper evaluation of dental state at lesions of dental tissue observed in children. The erosion of tooth hard tissue is characterized by various degrees of enamel abrasion, enamel discoloration, prisms and dentin tubules abrasion, yellowing of the dentin layer. As a result, erosive lesion of the dentin layer causes a pulp tissue inflammation, which in its turn leads to a complete loss of a tooth if the treatment is not applied in time [4]. A retrospective analysis of 2-5 years old children (495 patients) was performed according to the research theme and aim. Development and implementation of main principles in treatment and prophylaxis of erosion of tooth hard tissue in children was carried out. Objects and methods of the work. The research was performed at the Bukhara Regional Children’s Dental Clinic, by using a standard set of dental instruments and completing checklists for every patient. Erosive hotbeds of enamel were identified according to O’Sullivan Index. Results of the research and discussion. The prevalence rate of teeth erosion in 2-5 years old children was 29.9% (confidence interval 95% — 24.4–35.4). Considering external and internal factors in development of pathology, as well as taking into account modern studies and effectiveness of medications aimed at prevention of erosive lesion in treatment of primary teeth erosion in children, a three-stage complex of measures was implemented in practice. Such medications as fluocal gel (Fluocal gel, Fluocal solution, Septodont), calcium gluconate solution for injection (10%), ROKS gel (ROCS® Medical Minerals) were used for basic treatment. Biologically active substances as fuji glass-ionic cement (Fuji-IX, GC) and argetcem (VladMiVa) were used. On the base of data presented in the article, aconclusion is made that the complex of treatment-prophylactic measures described above can effectively help to reduce erosion lesion in children and to obtain normalized mineralization of the tooth hard tissue. Also, it is emphasized that the primary teeth erosion should be diagnosed correctly and in time so that to prevent of complications development and prevalence to healthy teeth. Taking into account seriousness of primary teeth erosion and need for further investigations, it is advisable to continue the research in development of modern treatment methods and prophylaxis ways of this pathology.